2017
DOI: 10.1371/journal.pone.0183575
|View full text |Cite
|
Sign up to set email alerts
|

Transetherification of 2,4-dimethoxynitrobenzene by aromatic nucleophilic substitution

Abstract: In view of the few reports concerning aromatic nucleophilic substitution reactions featuring an alkoxy group as a leaving group, the aromatic nucleophilic substitution of 2,4-dimethoxynitrobenzene was investigated with a bulky t-butoxide nucleophile under microwave irradiation. The transetherification of 2,4-dimethoxynitrobenezene with sodium t-butoxide under specific conditions, namely for 20 min at 110°C in 10% dimethoxyethane in toluene, afforded the desired product in 87% yield with exclusive ortho-selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The conditions for the regioselective S N Ar reaction in 2,4‐dihaloaromatics have been reported . Recently, we reported that the S N Ar reaction of 2,4‐dimethoxynitrobenzene ( 1 ) with a bulky nucleophile, sodium tert ‐butoxide afforded the desired product 2 (2‐ t ‐butoxy‐4‐methoxy nitrobenzene) in an excellent yield with exclusive ortho ‐selectivity under the optimized condition and the formation of the detectable byproduct 3 (2,4‐dimethoxy‐ N ‐(5‐methoxy‐2‐nitrophenyl) aniline) was elucidated using X‐ray crystallography . In our previous report, under the optimized condition without any additives, the formation of product 2 was limited, and an increase in the reaction time resulted in the decomposition of 2 and increased formation of the byproduct 3 (Table , entry 1).…”
Section: Effect Of Additives On Nucleophilic Substitutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conditions for the regioselective S N Ar reaction in 2,4‐dihaloaromatics have been reported . Recently, we reported that the S N Ar reaction of 2,4‐dimethoxynitrobenzene ( 1 ) with a bulky nucleophile, sodium tert ‐butoxide afforded the desired product 2 (2‐ t ‐butoxy‐4‐methoxy nitrobenzene) in an excellent yield with exclusive ortho ‐selectivity under the optimized condition and the formation of the detectable byproduct 3 (2,4‐dimethoxy‐ N ‐(5‐methoxy‐2‐nitrophenyl) aniline) was elucidated using X‐ray crystallography . In our previous report, under the optimized condition without any additives, the formation of product 2 was limited, and an increase in the reaction time resulted in the decomposition of 2 and increased formation of the byproduct 3 (Table , entry 1).…”
Section: Effect Of Additives On Nucleophilic Substitutionmentioning
confidence: 99%
“…A well‐known organocatalyst, thiourea/urea, and its analogues were explored to study their effect on the reaction. All reactions were carried out under microwave irradiation, according to our previous report . As shown in Table , the use of additives gave varied results, depending on the species and amount; e.g ., 0.1 equiv of thiourea afforded 2 in 53% and 78% yields for 20 and 30 min reaction times, respectively (Table , entry 3).…”
Section: Effect Of Additives On Nucleophilic Substitutionmentioning
confidence: 99%